Clinical investigation of respiratory system admittance in preschool children - Simpson, S.; Straszek, S.; Sly, P.; Stick, S.; Hall, Graham (Wiley-Liss, Inc, 2012)
Introduction: The upper airway shunt attenuates measurements of respiratory system impedance (Zrs), with greater impact in young children. Changes in respiratory system admittance, Ars (or Zrs−1), are theoretically independent of the shunt. This study compared the ability of Ars, to standard oscillatory outcomes, to determine respiratory disease and differentiate responses to inhaled bronchial challenges in the clinical setting. Methods: The forced oscillation technique (FOT) was used to establish reference equations for Ars in healthy preschool children, compare the change in Ars to standard oscillatory outcomes during bronchial challenge with inhaled adenosine-5′-monosphate (AMP) and to inhaled bronchodilator in healthy children and those with respiratory disease. Results: Children with respiratory disease had lower baseline Ars than healthy children (P  < 0.05). However, there was no improved ability for Ars to differentiate between bronchodilator responses in healthy and disease populations. In contrast, the response to inhaled AMP occurred at a lower concentration, [25 (3.12–400) mg ml−1; median (10th–90th centile)], as measured by Ars when compared to respiratory system resistance [225 (6.25–400) mg ml−1; P = 0.016]. Conclusion: This study supports the use of Ars during inhaled challenges, but not in response to bronchodilation. Pediatr Pulmonol. Pediatr Pulmonol. 2012; 47:53–58. © 2010 Wiley Periodicals, Inc.